The association between gut hormones and diet‐induced metabolic flexibility in metabolically healthy adults. Issue 1 (5th December 2022) - Unlu, Yigit; Vinales, Karyne L.; Hollstein, Tim; Chang, Douglas; Cabeza de Baca, Tomás; Walter, Mary; Krakoff, Jonathan; Piaggi, Paolo
Abstract: Objective: This study investigated whether interindividual variance in diet‐induced metabolic flexibility is explained by differences in gut hormone concentrations. Methods: A total of 69 healthy volunteers with normal glucose regulation underwent 24‐hour assessments of respiratory quotient (RQ) in a whole‐room indirect calorimeter during eucaloric feeding (EBL; 50% carbohydrate, 30% fat) and then, in a crossover design, during 24‐hour fasting and three normal‐protein (20%) overfeeding diets (200% energy requirements). Metabolic flexibility was defined as the change in 24‐hour RQ from EBL during standard (50% carbohydrate), high‐fat (60%), and high‐carbohydrate (75%) overfeeding diets. Plasma concentrations of glucagon‐like peptide‐1 (GLP‐1) and peptide YY (PYY) after an overnight fast were measured prior to and after each diet. Results: Compared with EBL, on average, 24‐hour RQ decreased by 4% during high‐fat overfeeding, whereas it increased by 4% during standard overfeeding and by 9% during high‐carbohydrate overfeeding. During high‐carbohydrate overfeeding, but not during any other overfeeding diet or fasting, increased GLP‐1 concentration was associated with increased RQ ( r = 0.44, p < 0.001), higher/lower carbohydrate/lipid oxidation rates ( r = 0.34 and r = −0.51, both p < 0.01), respectively, and increased plasma insulin concentration ( r = 0.38, p = 0.02). Conclusions: Increased GLP‐1 concentration following high‐carbohydrate overfeeding associated with a greater shift to carbohydrate oxidation, suggesting that GLP‐1 may be implicated in diet‐induced metabolic flexibility to carbohydrate overload.